Comparative Study of a Single-Incision Laparoscopic and a Conventional Laparoscopic Appendectomy for the Treatment of Acute Appendicitis - Kang, Jungwoo (The Korean Society of Coloproctology, 2012)
PURPOSE: For the treatment of acute appendicitis, a conventional laparoscopic appendectomy (LA) has been widely performed. Recently, the use of single incision laparoscopic surgery (SILS) is increasing because it is believed to have advantages over conventional laparoscopic surgery. In this study, we compared SILS and a conventional LA. METHODS: We analyzed the 217 patients who received laparoscopy-assisted appendectomies between August 2010 and April 2012 at Inje University Sanggye Paik Hospital. One hundred-twelve patients underwent SILS, and 105 patients underwent LA. For the two groups, we compared the operation times, postoperative laboratory results, postoperative pain, hospital stay, and postoperative complications. RESULTS: The patients' demographics, including body mass index, were not significantly different between the two groups. There were 6 perforated appendicitis cases in the SILS group and 5 cases in the LA group. The mean operative time in the SILS group was 65.88 ± 22.74 minutes whereas that in the LA group was 61.70 ± 22.27 minutes (P = 0.276). There were no significant differences in the mean hospital stays, use of nonsteroidal antiinflammatory drugs, and wound infections between the two groups. CONCLUSION: Postoperative pain, complications and hospital stay showed no statistically significant differences between the SILS and the LA groups. However, our SILS method uses a single trocar and two latex tubes, so cost savings and reduced interference during surgery are expected.